The relative efficacy of two exercise methods for older adults with chronic low back pain: A preliminary randomized control study. Issue 1 (17th April 2018) - Salas, Eric; Hulla, Ryan; Vanzzini, Nikeis; Trowbridge, Cynthia; Brotto, Marco; Keller, David; Gatchel, Robert J.
Abstract: The objective of the current study was to examine the relative efficacy of two exercise techniques—a multidimensional treatment (MDT) and a traditional senior exercise therapy treatment (TET)—in older adults diagnosed with chronic low back pain (CLBP). Participants ( N  = 16) were randomly assigned to either the MDT ( n  = 8) or TET ( n  = 8) groups after meeting the requirements for the presence of CLBP. Participants in the MDT group received an individualized exercise program, while participants in the TET participated in a group exercise program. A Mann–Whitney test was conducted to determine differences between psychosocial and physical variables pre‐ and post‐intervention. Statistical analyses indicated no significant differences in physical or psychosocial variables at pre‐intervention assessment. However, participants in the MDT group reported a decrease in fatigue and pain interference, with an increase in physical functioning, when compared to the TET group. Additionally, the MDT group displayed a significant decrease pain interference, while the TET group had an increase grip strength. Patients who received the MDT reported less fatigue and pain interference, and an increase in their overall physical functioning. Overall, the MDT was a more efficacious method to manage CLBP.